IMPLEMENTASI PERHITUNGAN PAJAK PENGHASILAN BADAN 2021 ATAS PP 23 TAHUN 2018 PADA PT D DILAKUKAN OLEH PT ARTA GEMILANG CONSULT - Reihan Safario Rosaldi, (2022)
This Final Project Report has the aim of developing the quality of students in applying the theories that have been obtained in the classroom and during internships in the work area. The Final Project Report was made for approximately 3 months at PT Arta Gemilang Consult with data collection techniques by interview and observation or direct observation, especially in the department. In order to obtain actual data related to Corporate Income Tax at PT Arta Gemilang Consult. Corporate Income Tax is a tax that determines by adding to the economy and is accepted by taxpayers who have businesses in Indonesia or abroad. The purpose of this Final Project Report is to find out the implementation of the Completion of Corporate Income Tax Return Calculation on PP 23 of 2018 which was carried out by PT Arta Gemilang Consult to PT D. Based on the results of field work practices, it can be concluded that the implementation of Calculating out the Corporate Income Tax Return for PP 23 of 2018 at PT D carried out by PT Arta Gemilang Consult was carried out in accordance with Law Number 36 of 2018.